Pengaruh Dimensi Kualitas Layanan Terhadap Kepuasan Mahasiswa Dimediasi Citra Kampus Pada Kampus STIEM Bongaya Makassar - Khaeril, Khaeril -; Alam, syamsul -; Themba, Orfyanny Syahreffy; Liline, Ledy jeane (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2024)
This research aims to analyze: (1) the direct effect of service quality dimensions on campus image; (2) the direct effect of service quality dimensions, campus image on student satisfaction; (3) the indirect effect of service quality dimensions on student satisfaction through campus image as a mediating variable.Research was desained with quantitative and theoretical confirmatory which respondents as many as 227 STIEM Bongaya students in the odd semester 2023-2004. Data was obtained by deploying Google Forms and analyzed using SEM SmartPLS version 3.Research results reveal that: (1) there are 2 dimensions of service quality that have positive and significant impact on campus image, namely assurance and tangible, while empathy, reliability, and responsiveness do not have a significant influence on the formation of campus image, even the dimensions of reliability and empathy also have negative coefficients on campus image; (2) Assurance, campus image, and tangibles have a positive and significant effect on student satisfaction, while reliability, responsiveness, and empathy do not have a significant effect, even responsiveness has a negative coefficient on student satisfaction; (3) The indirect effect of assurance and tanggible has positive and significant effect on student satisfaction through campus image variables. Indirect effect of responsiveness on student satisfaction through campus image has positive coefficient but is not significant. Futhermore, the indirect influence of empathy and reliability on student satisfaction through campus image has a negative coefficient, although not significant.